Irregularity molecular descriptors of VC5C7[m,n] and HC5C7[m,n] nanotubes - Munir, Muhammad Mobeen (Frontiers in Physics, 2022)
Scientific organization are creating carbon nanotube-based composite like VC_5 C_7 [m,n] and HC_5 C_7 [m,n] which indicate significant response against voltage. Imbalance based irregularity indices determining the degree of irregularity of a certain molecular structures and as a result determining the properties of molecular substance. We are interested in this article, we compute irregularity indices of two nanotubes, VC_5 C_7 [m,n] and HC_5 C_7 [m,n]. We produce formulas for irregularity of these two nanotubes, which are functions depending on parameters of the structure m and n. We compare our results graphically and conclude that VC_5 C_7 [m,n] is more irregular as compared to HC_5 C_7 [m,n].